Diffusion of the educational model and teacher participation in the peruvian university - Puente Saldaña, Rosa Ernestina (2025)
The objective of the study is to evaluate the relationship between the diffusion of the educational model and the level of participation of teachers in the Peruvian university. Today, we are required to have those documents that reflect the conception of university education and that correspond to the curricular structures with suitability. The educational model is one that shows the institutional identity, that guarantees a comprehensive education and that shows an important aspect that is sustainability, taken from one of the objectives of sustainable development: Quality education, if our purpose is to be in a scenario of success, then let's start with education (ODS, 2015). The design used in the methodological processes is non-experimental, with a type of applied research and an analytical method. The sample was represented by 120 university teachers, obtaining as a result a value of 0.581 according to the Rho the Spearman correlation. In this way, the null hypothesis is rejected and the postulated hypothesis is accepted.